2013
DOI: 10.1016/j.ejpoleco.2012.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Does aging affect preferences for welfare spending? A study of peoples' spending preferences in 22 countries, 1985–2006

Abstract: A recurrent assertion is that aging will intensify age-related conflict over public budget allocation. If people are led by their self-interest, the young will prioritize public education services, while the elderly will demand better pensions and health-care services. Addressing this issue requires longitudinal survey data and estimation of age (life-cycle), period and cohort effects. Except for a few of studies based on US data, such analyses are non-existent. We use repeated cross-section survey-data for 22… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
64
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(66 citation statements)
references
References 41 publications
1
64
0
1
Order By: Relevance
“…These life-cycle effects vary considerably across countries, but they are generally quite small. One limitation of the data used by Sørensen (2013) is that the alternatives available in the questionnaire for additional government expenditure are not mutually exclusive. In other words, individuals can choose to increase or decrease expenditure in all categories.…”
Section: A Review Of the Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…These life-cycle effects vary considerably across countries, but they are generally quite small. One limitation of the data used by Sørensen (2013) is that the alternatives available in the questionnaire for additional government expenditure are not mutually exclusive. In other words, individuals can choose to increase or decrease expenditure in all categories.…”
Section: A Review Of the Literaturementioning
confidence: 99%
“…Empirical evidence indeed underscores the importance of controlling for age and cohort effects. To our knowledge, the only paper that attempts to disentangle age, cohort and time effects in attitudes towards public spending priorities in European economies is Sørensen (2013). Using data from the International Social Survey Program (ISSP)which comprises four repeated cross-sectional sample surveys for the years 1985, 1990, 1996 and 2006 covering 22 countries, 16 of them in Europethe author finds that people do shift their spending priorities over their life cycle, but not by as much as cross-sectional age comparisons would suggest.…”
Section: Iii33 Age Effects or Cohort Effects?mentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decades, empirical studies have demonstrated that population aging in fact influences government spending components including social welfare, health and education (Harris et al, 2001;Krieger and Ruhose, 2013;Poterba, 1997;Sanz and Velázquez, 2007;Shelton, 2008;Tepe and Vanhuysse, 2009). Furthermore, evidence based on survey data reveals age-specific preferences regarding welfare and educational spending (Boeri et al, 2001;Bonoli and Häusermann, 2009;Cattaneo and Wolter, 2009;Sørensen, 2013). However, existing studies typically focus on different functions of government spending, but do not distinguish between consumption and investment.…”
Section: Philipp Jäger Torsten Schmidt 1 Introductionmentioning
confidence: 99%
“…The results for education expenditures, which entail similar characteristics as climate policies -short-term costs and long-term benefits -, seem to be rather clear, though. For instance, Cattaneo andWolter (2009), Rattsø andSørensen (2010), as well as Sørensen (2013) uniformly show that elderly people express a lower willingness to dedicate funds to education rather prefering health-and pension-related public expenditures. To our knowledge, the empirical literature on the consequences of population ageing for public goods provision has not addressed the issue of public spending on climate policy.…”
Section: Introductionmentioning
confidence: 99%